Environmental impact study on the special reserve area municipalities of Puerto Boyacá, Puerto Nary y Puerto Triunfo - Álvarez-Chaparro, Belkis Adriana (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
The present study's zone is located in the sector comprised by the municipalities of Puerrto Boyacá, Puerto Nare and Puerto Triunfo, to implement the enviromental impact study, was compiled some preexxisting information such as the geology, the geomorohology, the hydrogeology, the climatology, the socio-cultural and economic aspects of the area, infromation that was corroborated in the field . The characteriization of the material and the deposit (geologic and mining reserves) was carried out, later it took place a series of investigations, which resulted in the enviromental impact study, the mining project's delimitation area of influence was carried out, the communities were identified, some socialization meetings were held with the traditional miners, it was carried out as well held with the traditional miners, it was carried out as well a description, the characterization and analysis of the biotic, abiotic and socio-economic means affected by this project, also there were identified the impacts caused by the interaction between the mining work and the environment, by showing which are preventable, which can be corrected, mitigated or offset by the desing of the environmental management and contingency appropriate plans, inorder to obtain the enviromental license to allow the free development of the drag material extraction on the Special Reserve Area (ARE).